IMPLEMENTATION OF HOLISTIC EDUCATION THROUGH THE CAMPUS TEACHING PROGRAM BATCH 7 AT SDN NEGLAJAYA - Bildan Muhammad Sya'ban; Udin Supriadi; Nurti Budiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Holistic education plays a crucial role in optimizing student development. This study aims to identify the extent to which a holistic approach can be applied in the context of learning in elementary schools, with a focus on student growth. The research method used is qualitative, employing a case study approach that involves observations, interviews, and documentation. The findings reveal that the implementation of holistic education through learning activities that engage cognitive, affective, and psychomotor aspects can enhance students' knowledge, moral values, and skills. Furthermore, collaboration between university students and teachers is essential in creating an interactive learning environment. The results of this study indicate that the Teaching Campus program not only succeeded in transferring knowledge but also made significant contributions to character building and skill development of students at SDN Neglajaya. It is hoped that this program can provide recommendations and insights for policymakers to develop education more effectively in the future